PERBEDAAN KADAR INTERLEUKIN-6 PADA BERBAGAI STADIUM KLINIS KANKER PAYUDARA - , ANI USWATUN CHASANAH; , Dr. Andaru Dahesihdewi, M.Kes, SpPK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Breast cancer is one of diseases that cause morbidity and mortality. The prevalence of breast cancer is increasing worldwide including in Indonesia along with increased life expectancy, socioeconomic, and changes in disease patterns. More than half of patients with breast cancer is diagnosed in an advanced stage when the tumor has had metastasis to the handling tends to be late and only palliative. So far, interleukin-6, better known as cytokines that mediate inflammation and activation of lymphocytes hematopoesis, but recent studies reported IL-6 has a role as a mediator of tumor progression and correlated with the degree of tumor, and poor survival. This study was an observational analytic study with a cross-sectional design. The subjects in this study were patients with suspected breast cancer that visited Dr. Sardjito hospital in Yogyakarta who fullfilled the inclusion and exclusion criteria and collected consecutively. The level of IL-6 serum was determining using a quantitative sandwich electrochemiluminescence immunoassay method. Kruskal Wallis test and Mann Whitney test were used analyze the differences of IL-6 level between various clinical stage of the breast cancer. Fifty six breast cancer female patients, with an age mean of 47Â±10 years were eligible for this study. Most of breast cancer patients was stage IIIB 18 subjects (32,1%) and metastatic 37 people (66%). The results showed serum concentrations of IL-6 statistically higher in comparison with metastasis and non metastasis (622 vs. 1,99 pg / ml), p=0,001 which also correlated with clinical stage of breast cancer. The median level of IL-6 statistically higher in advanced stage compared with locally advanced and early stage (34,52 vs 4,82 vs 1,93 pg/ml). The median level of IL-6 increased proportionally with the stage of the cancer (the median level of IL-6 in stage I 1,64 pg/ml, stage IIA 1,87 pg/ml, stage IIB 2,47 pg/ml, stage IIIA 4,09 pg/ml, stage IIIB 6,09 pg/ml, stage IIIC 6,2 pg/ml dan stage IV 34,5 pg/ml). We observed that higher level concentration of serum IL-6 in advanced stage of breast cancer.